The Prototype Development of Digital Media Literacy with Sati (Mindfulness): A Literature Review for Card Game Ideation - Chaiveeradech, Monsak (Thammasat Review, 2024)
This article reviews the literature on self-literacy, media literacy, and the use of games as learning tools for acquiring those literacies. The article looks specifically at literature discussing the design of card games which aim to develop digital media literacy within a Thai cultural context by including the Thai Buddhist concept of sati (mindfulness). This review article focuses specifically on how the Thai concept of sati can be integrated into Western conceptual framing of digital media literacy which results in the ‘glocalising’ of media literacy through sati. This demonstrates that there can be diverse and culturally-sensitive approaches to the establishment of digital media literacy. Diverse approaches mean that every stakeholder can define their own digital media literacy and lead them to create their own effective approach for learning digital media literacy. The literature review for card game ideation development was used to initially explore a prototype of digital media literacy with the sati tool. The aim of the card game is to encourage players to cultivate the process of critical-reflection, which allows them to create a variety of tailored approaches from their own understanding on the concept of digital media literacy. This critical review article is a first step toward the design of a card game as a learning tool for understanding and acquiring digital media literacy with sati in a Thai cultural context, and to cultivate an internalised learning process through a card game.